Evaluasi Kinerja Finansial Sebagai Langkah Antisipasi Terhadap Potensi Kegagalan Keuangan - Alifia Marchellina; Satrio Bhamakerti (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
This research aims to investigate the importance of financial performance evaluation in predicting the potential financial failure of a business entity. Financial performance evaluation is a critical step in assessing a company's financial stability and health and in identifying early signs of potential bankruptcy. In this research, the financial performance analysis method is used to measure the company's financial health holistically. The research results highlight that proper financial performance evaluation can provide a clear view of potential future financial failures, enabling management to take appropriate anticipatory steps.